Pengaruh Model Discovery Learning pada Materi Zat Aditif dan Zat Adiktif terhadap Kemampuan Berpikir Kritis dan Hasil Belajar Siswa SMP - Revi Ristiani; S Sutarto; Ulin Nuha (Universitas Sarjanawiyata Tamansiswa, 2022)
The purpose of this observe is to decide the effect of the Discovery Learning model on the critical thinking skills and learning outcomes of junior high school students for additives and addictive substances. This have a look at is a quasi-experimental study experiment the usege of design non-equivalent control group design. The specimens in this study were classes VIIIA and VIIIB recognized by means of centered sampling. Quantitative data were acquired from pre-test and post-test results for critical thinking skills and learning outcomes, and then tested using an independent sample T-test. Data analysis revealed that the sig2 tail was greater than 0.05. This means that there is a difference between the mean of the experimental class and control class, and the mean of the experimental class is higher than control class. Based on the results of the study, it can be concluded that the Discovery Learning learning model has a great influence on the critical thinking ability and learning outcomes of junior high school students.